Social Media and Its Role in The Education Process of the University Students - Al-Ali, Fawzia (Advances in Social Sciences Research Journal, 2023)
This study seeks getting acquainted with media students’ opinions on the social media as an educational method, its merits, and demerits as well as the most apparent elements, which can be used within an educational curriculum on social media. Moreover, results of the study clarified that the most students’ attitudes towards social medias an educational method were negative; especially in terms of saying that teaching curricula on social media needs capabilities, which are unavailable in our universities, and their insufficient qualified professors in our universities to teach curricula on social media. This study is one of the descriptive studies, which aim at collecting data on the use of media students - the sample of the study - for social networking sites, their attitudes towards their use as an educational tool, as well as studying some variables related to employment such as gender, social status, this study is based on the survey methodology as a systematic scientific effort used to obtain information or descriptions of the phenomenon- subject of study. This study responds to the modern global concerns in the field of media, which seeks to benefit from the social media in teaching the subjects of media as being considered a media and communicational method in the first place as well as being an educational method in which the main constituents and elements of the modern educational methods are available.This study seeks to know the media students’ perspectives towards the social media as an educational method; their advantages, disadvantages and the most significant elements that can be employed within a curriculum on the social media. The researcher has chosen the Social Networking Sites as a model, as they include within their applications all the technical services that are provided by the Web today; such as the written text, multi-media, hypothetical communities and the methods of research and communication., which led to what is known as the educational communities on the Web, which historicize a new stage of human knowledge, known as (the Sustainable Communal Knowledge), which enables learners to employ the digital techniques that enable them to benefit one another through participating in building both the theoretical and applicable knowledge. Importance of Study: (1) Considered from the first Arabic studies, which attempt to know the possibility of employing the social media as an educational method. (2) Considered from the first Arabic studies, which attempt to deal with the social media as an educational and media method at the same time. (3) Seeking to clarify the educational and media constituents of the social media. (4) Seeking to know the perspectives of one of the important parties relevant to the employment of social media, which are the young people and the university students on the one hand and the media learners on the other hand.